The Difference Of Work Motivation In Self-Employment And Civil Servant - Arezah, Ersaliya (Journal of Islamic and Contemporary Psychology, 2023)
One of the reasons people work is to meet their daily needs. Individuals require encouragement or motivation to continue working, regardless of the type of work they are doing. The purpose of this research was to determine work motivation among individuals from two different work backgrounds: freelance work (self-employment) and bonded work as Civil Servants (PNS). This study took a qualitative method, with ERG theory serving as a guide for interviewees. The findings of this study revealed that both types of work can help subjects fulfil the aspects of existence and growth, but there are differences in the dynamics of motivation in the relatedness aspect between self-employment subjects and PNS subjects, with PNS subjects experiencing positive and negative social interactions with coworkers and superiors that self-employment subjects do not.